SEPARATION AGREEMENT ASSET FOR INDONESIAN CITIZENS MARRIED ABROAD - Bella Arwinilita; Siti Anggraini; Dwi Wisnu Wardana; Asep Hermawan; Setiawan Widiyoko (UNISSULA, 2021)
Legal protection in agreements on the separation of assets in marriage between Indonesian citizens and foreign citizens as well as analyzing the authority of a notary in making an agreement on the separation of assets in marriage between Indonesian citizens. and foreign nationals. This research uses empirical normative research. The approach method used is a statutory approach, conceptual approach and case approach. Based on the research results, it can be concluded that the making of a marriage contract can provide legal protection for the party who made it. The agreement deed made in the notary can be used as written evidence in court in case of problems at a later date. Based on Article 1868 of the Civil Code and notary authority in Article 15 of the notary office law, it is stated that notaries have the authority to make authentic deeds related to all agreements. Notaries must be able to provide legal certainty in people's lives because in the deed there is evidence that clearly determines a person's rights and obligations as a legal subject in society. Notary Deed as deed which has perfect evidentiary power makes the position of Notary Deed as the first and main evidence in civil evidentiary law.